2006
DOI: 10.4314/njsr.v7i3.12290
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiologic survey of maxillofacial fractures and concomitant injuries in Kaduna, Nigeria

Abstract: Background: There is an upward trend in facial injuries following changes in population pattern, increasing industrialization and urbanization, hence maxillofacial trauma is becoming a burden and a leading medical problem in emergency rooms worldwide. Method: A retrospective study of patients with maxillofacial fractures seen and treated at the Oral and Maxillofacial Unit, Ahmadu Bello University Teaching Hospital, Kaduna, Nigeria between January 1993 to January 2003. Data extracted from the patients' records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 21 publications
6
34
0
Order By: Relevance
“…13 In contrast, certain studies have revealed road traffic accidents to be the leading cause of maxillofacial trauma. 28,35,36 However, in this study, only 16% of the patients had suffered road traffic accidents. Only one patient had sustained maxillofacial injuries from a gunshot, whereas in other parts of South Africa maxillofacial gunshot wounds are a common finding.…”
Section: Discussionmentioning
confidence: 59%
“…13 In contrast, certain studies have revealed road traffic accidents to be the leading cause of maxillofacial trauma. 28,35,36 However, in this study, only 16% of the patients had suffered road traffic accidents. Only one patient had sustained maxillofacial injuries from a gunshot, whereas in other parts of South Africa maxillofacial gunshot wounds are a common finding.…”
Section: Discussionmentioning
confidence: 59%
“…The peak age of incidence of road traffic maxillofacial injuries reported in this study is consistent with literatures. 1,[7][8][9][10][11] The 21 to 40 years age group comprises the most active members of the society who are frequently engaged in commuting from one location to another and are therefore more exposed to the threat of RTC than any other age group. There was a male preponderance of 4.8:1 in this study which is far less than 16.9:1 reported by Adekeye, 7 but slightly greater than the 2.9:1 reported by Fasola et al 9 and 3.7:1 reported by Ajike et al 10 This shows that females are getting more involved in activities that expose them to RTC which may not be unconnected with the prevailing economic recession in the nation requiring more members of the family to be involved in sourcing for income for the family.…”
Section: Discussionmentioning
confidence: 99%
“…These high fatality rates could be a reason why Nigeria is leading other countries in RTC's fatality reported from WHO Afro region [5,6]. This study revealed that male gender and adults are mostly affected with RTCs [19][20][21] and could cause severe economic effects on household productivity because male genders are the usual breadwinners for households in Nigeria [22]. The proportion of fatal crashes in this study was similar to 28.6% reported in a study that analyzed RTCs between 1990 and 2012 [6].…”
Section: Discussionmentioning
confidence: 72%